2023
DOI: 10.2147/ijn.s433611
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Applications of Extracellular Vesicle for the Treatment of Skin Photoaging: A Comprehensive Review

Chan-Sheng Cai,
Gui-Juan He,
Fa-Wei Xu

Abstract: Skin photoaging is a complex biological process characterized by the accumulation of oxidative damage and structural changes in the skin, resulting from chronic exposure to ultraviolet (UV) radiation. Despite the growing demand for effective treatments, current therapeutic options for skin photoaging remain limited. However, emerging research has highlighted the potential of extracellular vesicles (EVs), including exosomes, micro-vesicles, apoptotic bodies and liposomes, as promising therapeutic agents in skin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
2

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 99 publications
1
2
2
Order By: Relevance
“…These effects have been well-documented in numerous in vitro studies. 36 With regards to skin melanin level, we did not find consistent results among instruments to draw conclusion about skin brightening efficacy of sEVs, though it has been reported in the literature. 45 Given the content profiling of our ASC-sEVs, we speculate that exogenous loading or complementation with compounds such as arbutin might be required for optimal whitening effect.…”
Section: Discussioncontrasting
confidence: 74%
See 3 more Smart Citations
“…These effects have been well-documented in numerous in vitro studies. 36 With regards to skin melanin level, we did not find consistent results among instruments to draw conclusion about skin brightening efficacy of sEVs, though it has been reported in the literature. 45 Given the content profiling of our ASC-sEVs, we speculate that exogenous loading or complementation with compounds such as arbutin might be required for optimal whitening effect.…”
Section: Discussioncontrasting
confidence: 74%
“…We observed that 70%–80% of total sEV proteins were identical among independent batches, higher than the reported 46.7% rate 12 . Functional analyses of biocargos confirmed the promising regenerative and anti‐inflammatory properties of ASC‐sEVs as already established 2,36 …”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…5 However, several clinical issues persist with these, warranting attention: (1) most commercial wound dressings would adhere to the wound site, causing tissue adhesion and discomfort when changing the dressing; 6,7 (2) according to previous research, the imbalance between oxidation and antioxidation during spontaneous physiological healing creates a destructive microenvironment when skin is damaged, 8,9 further causing cell damage and aging. 10 Therefore, designing a wound dressing that can guide the adhesion and proliferation of wound-repairing cells and regulate oxidative/antioxidative stress is an immediate requirement in clinical application.…”
Section: Introductionmentioning
confidence: 99%